An Analysis of The Image of Woman Based on Yukiguni Novel by Kawabata Yasunari - Ainsya Rakhmidianty Pramadityas; Idah Hamidah; Hartati Hartati (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2021)
This study is entitled with “An Analysis of the Image of Woman Based on Yukiguni Novel by Kawabata Yasunari” which purposes are to describe the characterization and the image of woman reflected on the main character, Komako. This is a qualitative descriptive study. The data are based on one of Kawabata Yasunari works, Yukiguni, 1971, which presented in narration and dialog to reflect the characterization and describe the image of woman from Komako. The data collecting method chosen is close reading technique (repeat reading). To analyse the finding, the method used in this study is narrative analysis. The findings of this study shown that the main woman character, Komako is described as a person who is easily offended, a drunkard, careless, yet neat. Her profession as Geisha displays a neat and beautiful physical image. Komako, either as a Geisha or Japanese woman, has a physic image who is easily offended, disliking liars, feeling guilty and careless. Other than that, she has a famous social image, as being well know by others, having a high sense of empathy, yet a rule breaker in which resulting her relationship between the environment she is living and herself as a person is inharmonious. To sum up, the physical images possessed by Komako is contrary with her psychic image and social.